2019
DOI: 10.1128/mbio.02205-19
|View full text |Cite
|
Sign up to set email alerts
|

Control of Bacillus subtilis Replication Initiation during Physiological Transitions and Perturbations

Abstract: High-throughput, quantitative approaches have enabled the discovery of fundamental principles describing bacterial physiology. These principles provide a foundation for predicting the behavior of biological systems, a widely held aspiration. However, these approaches are often exclusively applied to the best-known model organism, E. coli. In this report, we investigate to what extent quantitative principles discovered in Gram-negative E. coli are applicable to Gram-positive B. subtilis. We found that these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 62 publications
(113 reference statements)
5
67
0
Order By: Relevance
“…1 that their initiation-centric model is inconsistent with size homeostasis by the adder. We analyzed their simulations and found that they produced the adder-like behavior because of the additional fluctuations in the septum position (Figure S2A).Experimentally, septum position represents the most precise control among all measured single-cell parameters with CV < 5%Sauls et al 2019). Indeed, removing fluctuations in the septum position alone made the simulation deviated from experiment in a quantitative manner consistent with Eq.…”
mentioning
confidence: 56%
“…1 that their initiation-centric model is inconsistent with size homeostasis by the adder. We analyzed their simulations and found that they produced the adder-like behavior because of the additional fluctuations in the septum position (Figure S2A).Experimentally, septum position represents the most precise control among all measured single-cell parameters with CV < 5%Sauls et al 2019). Indeed, removing fluctuations in the septum position alone made the simulation deviated from experiment in a quantitative manner consistent with Eq.…”
mentioning
confidence: 56%
“…Quantifying the cell size and growth rates of Salmonella enterica grown in different nutrient media, Schaechter and colleagues discovered the nutrient growth law -bacterial cell size increases exponentially with the population growth rate [2]. High-throughput single-cell studies in recent years have confirmed this result for evolutionary divergent Escherichia coli and Bacillus subtilis [3][4][5][6], suggesting common strategies for bacterial cell size control. However, single-cell data show deviations from the nutrient growth law in experiments altering cellular proteomics [4,7], leaving open the connection between cell size, growth rate and protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the growth of S. enterica in different nutritional conditions, Schaechter et al discovered the nutrient growth law (5) -cell size increases exponentially with growth rate. Recent single-cell studies have confirmed this result for evolutionary divergent E. coli and B. subtilis (6,7). However, not all cell types change shapes the same way.…”
mentioning
confidence: 81%